Growth and development of school children - Vignerová, J; Bláha, P; Kobzová, J; Krejcovský, L; Paulová, M; Riedlová, J (Central European journal of public health, 2000)
With the support of the Internal Grant Agency of the Ministry of Health of the Czech Republic in 1997-1999 work proceeded on the grant "Semi-longitudinal study of the somatic growth of school children in the Czech Republic". The objective of this project is to assess the growth rate of the basic bodily characteristics in children and youth aged 6 to 14 years, to confirm the positive secular trend in height and body weight or its slowing or stagnation, and also to evaluate the growth and development of children under the new socio-economic conditions. In addition to thirty somatic characteristics which are assessed repeatedly every six months, in 1,925 children some supplementary data were obtained from parents. From hitherto assembled data ensues that there was no significant change of the mean length at birth nor of the birth weight as compared with 1989. The increase in height up to adolescence continues, in the higher age groups probably stagnation occurs. Despite a slight increase of mean body weight values since 1981, a gradual decline of the BMI values was observed. In boys this tendency is less marked than in girls, in particular in the oldest age groups. This trend was confirmed also by the results of the present investigation. As compared with the results of the 5th Nationwide Anthropological Survey in 1991 the group of overweight children, i.e. those above the 90th percentile of BMI comprises 6.9% boys and 8.9% girls from a total of almost 2,000 children, as compared with the expected 10%.
Keywords: Body Height; Female; dítě; předškolní dítě; Child Development; novorozenec; Birth Weight; Social Class; ženské pohlaví; vývoj dítěte; longitudinální studie; Adolescent; lidé; Infant, Newborn; porodní hmotnost; sběr dat; referenční hodnoty; tělesná výška; Male; Czech Republic; Reference Values; Data Collection; Child, Preschool; index tělesné hmotnosti; společenská třída; Česká republika; Child; mužské pohlaví; Body Mass Index; mladiství; Longitudinal Studies; Humans